Remission for Corruptors and the Challenges of Corruption Eradication in Indonesia - Herdian Malda Ksastria; Kadek Wiwik Indrayanti (Postgraduate University of Merdeka Malang, 2023)
Granting of remission for prisoners has been set in the Correctional Act 1995 (UU No. 12 Tahun 1995 Tentang Pemasyarakatan) and granting remission for corruptors has been set specifically in Government Regulation on the second amendment of Government Regulation No. 99 of 2012 on the requirements and procedures on granting the rights of the convicted person. However, this policy will injure the public’s sense of justice. It is because the corruption is harmful for the society and State, eventhough the law justifies on granting of remission for corruptors. From the point of view of human rights, corruption has been recognized as the violation of social and economic rights of the people. Therefore, corruption should no longer be classified as an ordinary crime, but extraordinary crime. The penalty for corruptors commonly tends to be mild from time to time, especially due to the granting of remission. The paper aims to discuss on the policy of granting remission for corruptors based on the philosophical, sociological, historical and juridical views. By using the normative qualitative method, the researcher found this policy has the challenges in corruption eradication in Indonesia because such policy is contrary with the spirit of government in corruption eradication in Indonesia and remission will remove the objective of sentencing.